Penerapan Ketertiban Umum Di Kota Gorontalo Menurut Peraturan Daerah No. 1 Tahun 2018 Tentang Ketertiban Umum - Haikal Pontoh (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Problem/Background: Public order and community peace is a description of a situation where people can carry out their daily activities in a calm, orderly and controlled manner, thus supporting the achievement of sustainable development in an area. There are many problems related to public order and peace, one of which occurs in Gorontalo City itself. In Gorontalo, there have been various violations of public order and order, such as violations of loose animals, violations of residence permits, street vendors, distribution of alcoholic drinks, violations of population management, vagrancy, beggars and street children, as well as perverted couples. boarding house. And the most frequent cases in Gorontalo City are violations related to the distribution of alcoholic drinks and exploitation of couples in boarding houses. Objective: The aim of this research is to find out how effective Satpol PP is in ensuring public peace and order i\\n Gorontalo City. Method: The method used in this research is a qualitative descriptive method, where an overview of facts and information in the field is obtained through data collection techniques, namely. observation, interviews and documentation. The sampling technique used purposive sampling and snowball sampling. Results/Findings: The results of this research indicate that maintaining public order and tranquility at the Gorontalo Satpol PP has not been effective. There are many influencing factors, such as the many inhibiting factors found during research.